Pengembangan Tortilla dan Biskuit Jagung Sebagai Produk Unggulan Desa Campor dan Sambiyan Kecamatan Konang Kabupaten Bangkalan Madura - Sarofa, Ulya Sarofa; Rosida, Rosida; Wicaksono, L. U. (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
Campor and Sambiyan village in Konang district had lime soil structure with sandy clay texture, so in thewinter the soil was sticky. The occupation of most people there were farming, animal, husbandary and fishing. One of theconsidered food agricultural crop of Campor and sambiyan village was corn plant. It was needed a social serviceProgram, such as RISMA (Research Result Implementation Grant for society) based on corn processing productinovation as famous product in Campor and Sambiyan vilage. The aim of this program was to improve people knowledgeand skill of corn flour processing into corn processing product (such as tortilla and corn biscuit) and to introduce properpackaging method and product marketing in accordance with corn processing development to increase people income.Monitoring and evaluation showed that the participants could do inovation on basic formulation by adding ingredients toenhance the product flavor and cryspines, packed and sold the products in smale scale marketing